The effects of infrastructure and public investment on the elasticity of private investment: an empirical investigation for Brazil - JEFFERSON S. FRAGA; HELDER LARA FERREIRA-FILHO (Brazilian Journal of Political Economy, 2023)
ABSTRACT This study estimates the determinants of the elasticities of private investment and total investment for the Brazilian economy for the period between 1960 and 2013. It uses a Bayesian model averaging and weighted-average least-squares approach with a flexible accelerator model of investment equation and Kalman filtering techniques. We conclude that the aggregate infrastructure index (taken from the main component analysis) and public investment crowd-in private investment. The results indicate that private investment is constrained by the availability of bank credit. Furthermore, we find that infrastructure stock and public investment are two of the main determinants of the elasticities of private investment. This demonstrates that public investment, mainly in infrastructure, is of great importance in raising the sensitivity of private investment in the Brazilian economy.